Can environmental information disclosure reduce air pollution? Evidence from China - Xiong, Lei; Long, Hongyu; Zhang, Xiang; Yu, Chenyang; Wen, Zezhou (Frontiers in Environmental Science, 2023)
Previous studies have focused on the reduction effect of regulation-based instruments and economic-based instruments on air pollution, ignoring the importance of environmental information disclosure. Based on the Ambient Air Quality Standards (AAQS), a quasi-natural policy implemented in 2012, this paper assesses the effect of environmental information disclosure on air pollution through a dynamic spatial difference-in-difference (DID) model using panel data of 269 cities from 2006 to 2017 in China. We find that the implementation of the AAQS results in a 3% reduction of local PM2.5 concentration and a 3.3% reduction of PM2.5 concentration in the surrounding cities. Further analysis suggests that environmental information disclosure reduces air pollution through enhancing public environmental concerns, green innovation, and industrial upgrading. We also explore the moderating effect of government environmental regulation and heterogeneity analysis in different regions. Our findings suggest that government should further develop the scope and quality of environmental quality information disclosure. Moreover, the local government should provide more support for the green transformation of enterprises and provide necessary support during the transition period. In addition, long-term sustainable environmental protection policies must be able to mobilize regional initiatives for green development.